The effect of coating chitosan on Porphyromonas gingivalis biofilm formation in the surface of orthodontic mini-implant - Haru Setyo Anggani; Renaldo Guruh Perdana; Erwin Siregar; Endang Winiati Bachtiar (Wolters Kluwer Medknow Publications, 2021)
Infection is the main problem for the failure of orthodontic mini-implant. Modern prevention of infection is now focused on local antibacterial coatings on implant devices. Chitosan is biocompatible and has antibacterial properties. Azithromycin is a synthetic antibiotic with immunomodulatory properties in which it has an advantage over the rest of antibiotics. This study aimed to evaluate the effect coating chitosan on the orthodontic mini-implant in Porphyromonas gingivalis biofilm formation. This is an experimental study using 25 orthodontic mini-implants. Five samples were coated with chitosan, 5 samples were coated with chitosan-azithromycin, 5 samples were coated with azithromycin, 5 samples were uncoated, and 5 samples were uncoated and were not exposed to P. gingivalis. P. gingivalis biofilms on the surface of the orthodontic mini-implant were observed after 24 h of incubation. P. gingivalis biofilm mass inhibition was highest in the azithromycin-treated group, followed by chitosan + azithromycin and chitosan only. The one-way ANOVA statistic test and post hoc Bonferroni statistic test of P. gingivalis biofilm mass show a significant difference between and within groups of experiments (P < 0.05). The Pearson correlation test with a value of R = +0.88, indicated that the bacterial viability count and the biofilm mass have a strong positive correlation. In conclusion, orthodontic mini-implant coated with chitosan, chitosan with azithromycin, or azithromycin only effectively suppressed P. gingivalis biofilm formation.